Pengaruh Citra Merek Dan Kualitas Produk Terhadap Keputusan Pembelian Konsumen Pada PT.Sumber Alfaria Trijaya Tbk(Alfamart) Bengkulu - Syallaysyah, Jenny Dwi; Nasution, Suswati; Abi, Yudi Irawan (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2024)
This research aims to analyze the influence of brand image and product quality on consumer purchasing decisions at PT. Sumber Alfaria Trijaya Tbk (Alfamart) Bengkulu. The research method used was a quantitative method by distributing questionnaires to 51 respondents who were Alfamart customers in Bengkulu. Data were analyzed using multiple linear regression to find out how much influence brand image and product quality have on purchasing decisions. The research results show Y= 0.942+0.291X1 +0.452X2+e with an R square result of 0.487, this means that brand image and product quality have a 48.7% influence on purchasing decisions and the remaining 51.3% is determined by other factors. The significant values ​​obtained were 0.012 (X1) and 0.004 (X2), both of which were smaller than 0.05. X1, X2 simultaneously equal to 0.000 (smaller than 0.05) influence purchasing decisions.